Causally treatable, hereditary neuropathies in Fabry's disease, transthyretin‐related familial amyloidosis, and Pompe's disease. (12th March 2017) - Finsterer, J.; Wanschitz, J.; Quasthoff, S.; Iglseder, S.; Löscher, W.; Grisold, W.
Abstract : Objectives: Most acquired neuropathies are treatable, whereas genetic neuropathies respond to treatment in Fabry's disease (FD), transthyretin‐related familial amyloidosis (TTR‐FA), and Pompe's disease (PD). This review summarizes and discusses recent findings and future perspectives concerning etiology, pathophysiology, clinical presentation, diagnosis, treatment, and outcome of neuropathy in FD, TTR‐FA, and PD. Methods: Literature review. Results: Neuropathy in FD concerns particularly small, unmyelinated, or myelinated sensory fibers (small fiber neuropathy [SFN]) and autonomic fibers, manifesting as acroparesthesias, Fabry's crises, or autonomous disturbances. FD neuropathy benefits from agalsidase alpha (0.2 mg/kg every second week intravenously) or from beta (1.0 mg/kg every second week intravenously). Neuropathy in TTR‐FA is axonal and affects large and small sensory, motor, and autonomous fibers. Neuropathy in TTR‐FA profits from liver transplantation and the TTR kinetic stabilizer tafamidis (20 mg/d). Neuropathy in PD particularly occurs in late‐onset PD and manifests as mononeuropathy, polyneuropathy, or SFN. PD neuropathy presumably responds to alglucosidase‐alpha (20 mg/kg every second week intravenously). Conclusions: Neuropathy in FD, TTR‐FA, and PD is predominantly a SFN and can be the dominant feature in FD and TTR‐FA. SFN in FD, TTR‐FA, and PD needs to be recognized and benefits from enzyme replacement treatment or TT‐kinetic stabilizers.